Factors Related to the Implementation of Hospital Management Information System (SIMRS) at the Kendari City Regional General Hospital - Chivansa, Firsta Wahyuni; Saafi, La Ode; Rasyid, Sri Anggarini; Risky, Sartini (Waluya The International Science of Health Journal, 2025)
Introduction: The Hospital Management Information System (SIMRS) has been used at Kendari City Hospital. The use of the Hospital Management Information System (SIMRS) has several obstacles including the Integrated Patient Development Record (CPPT) which is constrained by the network and slow internet network and the limited availability of computers and printers so that it is necessary to analyze factors related to the implementation of the Hospital Management Information System (SIMRS) at the Kendari City Regional General Hospital. Method: This type of research uses an observational design and is used as descriptive with a quantitative approach. Analytically, the data from the measurement of variables was carried out using descriptive analysis, inferential analysis, mutivariate analysis to find out the factors related to the implementation of the Hospital Management Information System (SIMRS) at Kendari City Hospital. Result: The respondents' behavior related to people, organization, technology and net benefits had a value below the significant level (<0.05) and a chi-square test value of <3,841, so that the criteria showed that there was no significant relationship with the implementation of SIMRS. Conclusion: The conclusion in this journal. There was no significant relationship between people, organizations, technology and net benefits to the implementation of SIMRS at Kendari Hospital.